The quantity and nutritive quality of Vallisneria americana biomass, in navigation pool no. 9 of the Upper Mississippi River - Donnermeyer, Gary N. (My University, 1982)
Vallisneria americana Michx. (wild celery) was studied to determine biomass, productivity, and the nutritive potential of all morphological structures. The study area was located in the southern portion of Navigation Pool No. 9 of the Upper Mississippi River. A 2.6 hectare (0.1 mi squared) stand of monotypic V. americana was selected for study. Sampling was done monthly or bi-monthly during the summer and autumn of 1980 and the spring and summer of 1981. The nutritive potential of V. americana was assessed from these samples by determining dry matter, neutral-detergent fiber, crude protein, ash, and caloric concentrations of each plant organ.
Keywords: Mississippi River; American wildcelery